Lactic acid and methane: Improved exploitation of biowaste potential. (January 2015) - Dreschke, G.; Probst, M.; Walter, A.; Pümpel, T.; Walde, J.; Insam, H.
Highlights: Municipal organic solid waste is suitable for lactic acid production. Lactic acid yield can be enhanced by lactic acid extraction during fermentation. Optimal fermentation period of 24 h for lactic acid production. Lactobacilli can be enriched to over 70% of the bacterial community. High biomethane potential of lactic acid fermentation residues. Abstract: This feasibility study investigated a two-step biorefining approach to increase the value gained by recycling of organic municipal solid waste. Firstly, lactic acid was produced via batch fermentation at 37 °C using the indigenous microbiome. Experiments revealed an optimal fermentation period of 24 h resulting in high yields of lactic acid (up to 37 g kg −1 ). The lactic acid proportion of total volatile fatty acid content reached up to 83%. Lactobacilli were selectively enriched to up to 75% of the bacterial community. Additionally conversion of organic matter to lactic acid was increased from 22% to 30% through counteracting end product inhibition by continuous lactic acid extraction. Secondly, fermentation residues were used as co-substrate in biomethane production yielding up to 618 ± 41 Nml biomethane g −1 volatile solids. Digestate, the only end product of this process can be used as organic fertilizer.